Energy potential of coffee processing residues combined with charcoal fines (Research, Society and Development, 2021)
The objective of the present work was to evaluate the composition and quality of coffee processing residues and their mixtures with charcoal fines for energy purposes. The coffee biomass, charcoal fines and mixtures (10, 20 and 30% of charcoal fines) were characterized for moisture, immediate and elemental chemical composition, gross and liquid heating value, and bulk and energy density. The inclusion of charcoal fines promoted a significant reduction in the moisture content of the coffee lignocellulosic biomass, as well as an increase in the energy properties. The treatment with 30% charcoal fines presented the best quality, reaching a higher calorific value of 19.44 MJ.Kg-1 and liquid heating value of 16.75 MJ.Kg-1, that is, an energy increase of 6 and 10%, respectively, compared to the treatment with 100% coffee waste biomass. The physicochemical characteristics of both the residues generated during coffee processing and the coal fines show good energetic properties, which make them an excellent material for use in the development of biofuels. Therefore, it is recommended to mix at least 20% of charcoal fines to enhance the energy performance of residues from coffee production.